a) (+5)-(+11) =
b) (-5)-(+8) =
c) (+7)-(+1)=
d) (-10)-(-10)=
e) (-3)-(-5)=
f) (+15)-(-19)=
Usuário anônimo:
oi
Soluções para a tarefa
Respondido por
1
Resposta:
a) (+5)-(+11) =6
b) (-5)-(+8) =13
c) (+7)-(+1)=6
d) (-10)-(-10)=0
e) (-3)-(-5)=2
f) (+15)-(-19)=34
Explicação passo-a-passo:
espero ter ajudado
Perguntas interessantes
Português,
8 meses atrás
Contabilidade,
8 meses atrás
Geografia,
8 meses atrás
Sociologia,
9 meses atrás
Português,
9 meses atrás
Português,
1 ano atrás
Matemática,
1 ano atrás